Hereditary Motor and Sensory Neuropathies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Transcranial magnetic brain stimulation was used to study central motor conduction (CMCT) to small hand muscles in patients with peroneal muscular atrophy and hereditary spastic paraplegia at the National Hospital and Institute of Neurology, Queen Square and the Department of Neurological Science, Royal Free Hospital, London, UK.